A tunable sub-wavelength acoustic imaging planar metalens. (9th March 2023) - Zuo, Gang; Huang, Zhen; Ma, Fuyin
Abstract: Acoustic metamaterials can be used to fabricate metalenses that can achieve sub-wavelength imaging resolution, but the reported devices are often passive and cannot adapt to changes in working frequency. To this end, we propose a dynamic tunable acoustic imaging planar metalens by introducing a telescopic tube between two sets of perforated Fabry–Pérot resonant metamaterial lenses to adjust the combined length of the imaging hole. Since the working frequency of the Fabry–Pérot resonant structure is directly related to the thickness of the metalens, continuous adjustment of the working frequency can be achieved by continuously changing the length of the imaging hole. This Fabry–Pérot resonant perforated structure belongs to an acoustic metamaterial unit, which can be resonantly coupled with evanescent waves to enhance the evanescent waves carrying detailed information of objects, thereby realizing high-resolution imaging. Relying on the resonance tunneling effect of the imaging hole, high acoustic transmittance can be obtained at the working frequency, ensuring excellent imaging quality. Through numerical calculation and experimental measurement results, the imaging performance and tunability of the tunable sub-wavelength acoustic imaging metalens are demonstrated. The proposed tunable acoustic planar metalens overcomes the shortcomings of the fixed working frequency of passive metalenses and has potential applications in the fields of ultrasound imaging and medical diagnosis.